2020
DOI: 10.1200/jco.2020.38.15_suppl.9016
|View full text |Cite
|
Sign up to set email alerts
|

SAKK 16/14: Anti-PD-L1 antibody durvalumab in addition to neoadjuvant chemotherapy in patients with stage IIIA(N2) non-small cell lung cancer (NSCLC)—A multicenter single-arm phase II trial.

Abstract: 9016 Background: For patients (pts) with resectable stage IIIA(N2) non-small cell lung cancer (NSCLC) neoadjuvant chemotherapy (chemo) with 3 cycles cisplatin (cis)/docetaxel (doc) followed by surgery is an accepted standard of care leading to a 1-year (yr) event-free survival (EFS) of 48% and a 5-yr overall survival (OS) of 37%. PD-1/PD-L1 inhibitors have recently shown to lead to high response rates in resectable NSCLC. Methods: SAKK 16/14 is an open-label single-arm phase II study including 68 pts with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In an exploratory trial of patients with stage IIIA resectable NSCLC treated with platinum‐based CTx plus nivolumab before undergoing surgery ( n = 13), the overall response rate was approximately 85%, with 9 patients (69.2%) achieving complete pathological response (95% CI, 38.6–90.9%) [66]. The SAKK 16/14 trial demonstrated a 1‐year event‐free survival rate of 73.3% with CTx and durvalumab, followed by surgery and 12 months of postoperative durvalumab, in patients with resectable stage IIIA NSCLC [67]. The TOP 1501 trial features patients with stage IB, II, or IIIA NSCLC being treated with neoadjuvant pembrolizumab monotherapy, followed by postoperative CTx and pembrolizumab [7].…”
Section: Mdt Treatment Choicesmentioning
confidence: 99%
“…In an exploratory trial of patients with stage IIIA resectable NSCLC treated with platinum‐based CTx plus nivolumab before undergoing surgery ( n = 13), the overall response rate was approximately 85%, with 9 patients (69.2%) achieving complete pathological response (95% CI, 38.6–90.9%) [66]. The SAKK 16/14 trial demonstrated a 1‐year event‐free survival rate of 73.3% with CTx and durvalumab, followed by surgery and 12 months of postoperative durvalumab, in patients with resectable stage IIIA NSCLC [67]. The TOP 1501 trial features patients with stage IB, II, or IIIA NSCLC being treated with neoadjuvant pembrolizumab monotherapy, followed by postoperative CTx and pembrolizumab [7].…”
Section: Mdt Treatment Choicesmentioning
confidence: 99%
“…In the same year, previous results from the NEOSTAR study (28), a preoperative phase II study of nivolumab plus ipilimumab, and results from the MK3475-223 study (29), a phase I study of pembrolizumab, were reported, both of which had similar safety and MPR values of 20-30%. Other Phase II and Ib studies of various drugs (atezolizumab and durvalumab, an anti-PD-L1 antibody, and sintilimab, a recently emerging anti-PD-1 antibody) in combination with chemotherapy have been reported, all of which have shown similar results (30)(31)(32).…”
Section: Perioperative Treatment With Molecular Targeted Agentsmentioning
confidence: 87%
“…Immunotherapy in combination with chemotherapy was found to be safe in the neoadjuvant setting. The one-year event-free survival rate was 73.3% [ 34 ].…”
Section: Neoadjuvant Immunotherapymentioning
confidence: 99%